2016
DOI: 10.1002/ajmg.b.32500
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in 7‐year‐old children: Differences in maternal and paternal ratings and the genetic epidemiology

Abstract: The assessment of children's psychopathology is often based on parental report. Earlier studies have suggested that rater bias can affect the estimates of genetic, shared environmental and unique environmental influences on differences between children. The availability of a large dataset of maternal as well as paternal ratings of psychopathology in 7‐year old children enabled (i) the analysis of informant effects on these assessments, and (ii) to obtain more reliable estimates of the genetic and non‐genetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…In line with earlier studies, the heritability of childhood and adolescent conduct problems and adult antisocial personality problems is substantial (between 43% and 49%) [ 10 13 , 40 , 41 ], and genetic factors are the main contributor to covariation across the ages [ 14 17 ]. In agreement with an earlier study in 7-year-old Dutch twins, the influence of the shared environment on conduct problems in childhood was large (44%) [ 30 ]. Strikingly, the shared environmental effect was non-significant during adolescence and adulthood, while the sample sizes (6839 adolescent twin pairs and 7909 adult twin pairs, overlap of 3977 twin pairs) were sufficiently large to detect shared environmental influences [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with earlier studies, the heritability of childhood and adolescent conduct problems and adult antisocial personality problems is substantial (between 43% and 49%) [ 10 13 , 40 , 41 ], and genetic factors are the main contributor to covariation across the ages [ 14 17 ]. In agreement with an earlier study in 7-year-old Dutch twins, the influence of the shared environment on conduct problems in childhood was large (44%) [ 30 ]. Strikingly, the shared environmental effect was non-significant during adolescence and adulthood, while the sample sizes (6839 adolescent twin pairs and 7909 adult twin pairs, overlap of 3977 twin pairs) were sufficiently large to detect shared environmental influences [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…The sample included 60 pairs between age 8.7–9 years and 10 pairs who had reached age 12 years when their parents completed the survey, throughout the paper, we refer to this group as 9–10-year-olds. Paternal reports were not included; an earlier study of these twins at age 7 showed that heritability estimates for conduct problems did not differ between paternal and maternal reports [ 30 ]. For the 13–18-year-old adolescent twins, self-report data from birth cohorts 1986–1999 were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies in childhood are limited to parent reports, and more research including multiple informants (i.e. parent-, self-and teacher-report) at the same age is necessary to distill whether the absence of C is specific to self-control or the result of reporter effects (Bartels et al, 2007;Wesseldijk et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, in adolescence and adulthood, both MZ and DZ correlations decreased, resulting in MZ correlations being larger than twice the DZ correlations, suggesting a role for dominant genetic effects besides additive genetic effects. We recognize that this might be a methodological artifact as a result of the difference between parent rating (e.g., parents phenotype possibly contribute to similar ratings for both twins resulting in shared environmental influences) and self-rating scores (e.g., a twin's own genetic architecture contributing to their own behavior and therefore self-rating scores on well-being and depressive symptoms) ( 48 , 64 66 ). However, while differences in parent reports and child reports exist, earlier studies have illustrated sufficient agreement between child and parent reports on children's quality of life ( 67 ).…”
Section: Limitationsmentioning
confidence: 99%